EFFECT OF ADDING ULTRA FINE BUBBLE TO DIESEL AND BIODIESEL FUEL ON TWO WHEEL TRACTORS DIESEL ENGINE PERFORMANCE - Sam Herodian (Testing Center for Oil and Gas LEMIGAS, 2025)
Diesel engines have advantages in their use in various sectors, one of which is that they have high torque and power to cover heavy loads optimally. The fuel used in a diesel engine has a big impact on the performance produced by the diesel engine. Many fuel refinements have been carried out using various methods. The aim of this research is to test and analyze one method of improving Ultra Fine Bubble combustion in various diesel fuels. Ultra fine bubble is a method of adding nano-sized oxygen to fuel which is expected to improve engine performance. The method used is a performance test on a hand tractor axle dynamometer with B0 (diesel), B35 (biodiesel–diesel blends 35%) and biodiesel fuel. When adding UFB, differences in characteristic values ​​are produced in cetane number, fog point, lubricity, density, viscosity and flash point. The power produced on B0 fuel when given UFB increased by 3.46%, on B35 UFB increased by 7.45% and on biodiesel UFB increased by 1.6%. The increase in power that occurs in B35 and biodiesel is also followed by a decrease in the specific fuel consumption (sfc) value, while in B0 there is an increase in sfc when the fuel is given UFB.